Pre-sleep arousal as a possible mechanism driving sleep problems in relation to ADHD traits - Daniel Smullen; Tamar Kolodny; Andrew P. Bagshaw; Carmel Mevorach (Scientific Reports)
Abstract Attention Deficit Hyperactivity Disorder (ADHD) is inextricably linked with sleep problems. Clinically diagnosed poor sleep is common in ADHD, and subclinical sleep difficulties are frequently reported. However, the mechanisms which underly poor sleep in ADHD are poorly understood. Since one of the most consistently reported sleep difficulties is sleep initiation, it is plausible that pre-sleep arousal plays an important role, but this has not been confirmed. We investigated this by assessing neurotypical adult participants’ self-reported perceptions of their sleep difficulties and pre-sleep arousal in relation to their ADHD-like traits. We acquired two independent datasets: an online dataset (n = 104) and an in-person replication dataset (n = 96). We first assessed the association between ADHD-like traits and sleep quality generally, as well as sleep-onset problems specifically. We then tested the extent to which pre-sleep arousal mediated the association between ADHD traits and sleep initiation problems. There was a clear association in both datasets between ADHD-like traits and their sleep quality – high expression of ADHD-like behaviours coincided with reduced sleep quality. This relationship was largely mediated by the levels of pre-sleep arousal: the link between ADHD-like traits and sleep quality was explained by the relationship between ADHD and (primarily cognitive) pre-sleep arousal. Our findings highlight the role of pre-sleep arousal in the relationship between ADHD-like traits and sleep quality, which could direct future interventions.